Looking at the Pretty “Phase” of Membraneless Organelles: A View From Drosophila Glia - Arkov, Alexey L. (Frontiers in Cell and Developmental Biology, 2022)
Membraneless granules assemble in different cell types and cellular loci and are the focus of intense research due to their fundamental importance for cellular organization. These dynamic organelles are commonly assembled from RNA and protein components and exhibit soft matter characteristics of molecular condensates currently characterized with biophysical approaches and super-resolution microscopy imaging. In addition, research on the molecular mechanisms of the RNA–protein granules assembly provided insights into the formation of abnormal granules and molecular aggregates, which takes place during many neurodegenerative disorders including Parkinson’s diseases (PD), Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS), and frontotemporal dementia (FTD). While these disorders are associated with formation of abnormal granules, membraneless organelles are normally assembled in neurons and contribute to translational control and affect stability of neuronal RNAs. More recently, a new subtype of membraneless granules was identified in Drosophila glia (glial granules). Interestingly, glial granules were found to contain proteins which are the principal components of the membraneless granules in germ cells (germ granules), indicating some similarity in the functional assembly of these structures in glia and germline. This mini review highlights recent research on glial granules in the context of other membraneless organelles, including their assembly mechanisms and potential functions in the nervous system.